Development of a simulated assessment center - LIEVENS, Filip (Institutional Knowledge at Singapore Management University, 1999)
In this study a simulation of an assessment center is developed consisting of videotaped performances of four candidates in three exercises: sales presentation, role-play, and group discussion. To develop the simulation, candidate profiles are constructed which vary along three dimensions: problem analysis and problem solving, interpersonal sensitivity, and planning and organizing. Dimension-specific behaviors are adapted from 173 critical incidents provided by 20 experienced assessors. As a result, scripts are written and enacted by actors. To validate the simulation, experienced assessors evaluate all candidates under optimal conditions. High interrater agreement among these experts (intraclass conelation = .9) and a high correlation (r = .93) between expert scores and intended scores are found. Finally, the simulation is piloted and calibrated on 16 managers and 28 industrial-psychology students. Practical applications of the simulation involve assessor training and certification. Researchers may use it to examine which factors affect the accuracy of assessor judgments.